Description of a new species of Aporrhais (Gastropoda, Stromboidea) from the Upper Eocene of Western Siberia - Ulrich Wieneke; Pavel V. Smirnov; Anton Maslennikov; Yaroslav S. Trubin (Zitteliana)
Material from the Upper Eocene Tavda Formation of Western Siberia contains a new species, Aporrhais siberica sp. nov. It has been misidentified as A. cornuta Korobkov, 1949, an aporrhaid originally described from the Upper Eocene / Lower Oligocene of the Turan Sea. The main difference between A. siberica and A. cornuta is the missing spire-adnate digitation of A. siberica. Publications referencing both morphologies are analyzed, and revised synonymies are presented.